Kuantan clay subgrade stabilization by using carpet fibers as stabilizer - Wahida, Mat Zin (2012)
The use of carpet fiber as stabilizer for soil stabilization is attractive approach with such low cost material and reduced needs for landfihling. The main objective of the study is the utilization of carpet fibers to improve soil subgrade for highway construction. The research conducts various contents of carpet fibres to clay soils from Kampung Ubai, Kuantan-Pekan. The compaction tests and California Bearing Ratio (CBR) tests we applied in soil samples to estimate the optimum mixture design. The samples were set up by mixing soil samples with various content of carpet fibers at different water content in compaction test to obtain optimum dry unit weight and optimum water contents. The optimum water contents were used in CBR test s of mixtures of soil samples-carpet fibers. The accomplishment of subgrade stabilization depends on the engineering properties of soils and the content of carpet fibers. The performance analysis of carpet fiber should be based on the laboratory tests such as engineering properties of soil and CBR tests of specified site in Kuantan. The strength gain in stabilization mainly depends on two factors: carpet fiber content and molding water content. The optimum carpet fibers that give the optimum strength is 9%. The variation content of carpet fibers were 3%, 6% and 9% by total weight.